Development of biodegradable films from lesser yam (Dioscorea esculenta) starch. - Valdevieso, Ysobelle B. (2023.)
To reduce the plastic pollution caused by accumulation of non-biodegradable materials, research has been geared towards developing biodegradable films. Starch is one of the appealing raw materials for biodegradable films. Lesser yam (Dioscorea esculenta) is one of the many tubers in the Philippines that contains 24.8% starch. The objective of the study was to create starch biodegradable films using lesser yam starch and characterize their mechanical, physicochemical, and barrier characteristics. For extraction of starch, samples were prepared, cut into small pieces, and mucilage was removed. Multiple homogenizing, followed by filtering was done. Ethanol-aided precipitation was used to accelerate drying and purification of starch. Starch-glycerin formulations were heated to 90°C and cast into molds. Solutions were dried and cooled off. For physicochemical properties, water activity of the formulated films was in the range of 0.849 - 0.841. While the thickness of the film formulations ranges from 0.17 mm - 0.19 mm. Lastly, moisture content values ranged from 23.58% to 35.59%. For the mechanical properties, the hardness of the films ranges from 42.5 g - 62.5 g. Meanwhile, the elongation values range from 7.572 mm to 16.223 mm. Lastly, for the barrier properties the obtained values for WVP values ranges from 7.133 x10-12 g/Pa·s·m - 6.978 x10-12 g/Pa·s·m. The water solubility of the film formulations ranges from 2.47% to 4.56%. Based on the results, lesser yam starch can be used to produce biodegradable films. It was also found out that glycerin and starch concentrations influence the different properties of the films.
Thesis (Undergraduate, Bachelor of Science in Food Technology) School of Technology, University of the Philippines Visayas, Miagao, Iloilo. 2023.
Keywords: Films -- Biodegradable; Lesser yam starch